Therapeutic potential and ownership of commercially available consoles in children with cerebral palsy. (February 2017) - Farr, William; Green, Dido; Male, Ian; Morris, Christopher; Bailey, Sarah; Gage, Heather; Speller, Sandra; Colville, Val; Jackson, Mandy; Bremner, Stephen; Memon, Anjum
Introduction: We conducted a survey amongst families of children with cerebral palsy to ascertain the ownership and therapeutic use and potential of commercial games consoles to improve motor function. Method: Three hundred families in South East England were identified through clinical records, and were requested to complete an anonymised questionnaire. Results: A total of 61 families (20% response) returned a completed questionnaire with 41 (68%) identified males and 19 (32%) identified females with cerebral palsy, with a mean age of 11 years 5 months (SD 3Y 7M). The large majority of families, 59 (97%), owned a commercial console and the child used this for 50–300 minutes a week. Returns by severity of motor impairment were: Gross Motor Function Classification System I (22%), II (32%), III (13%), IV (15%), V (18%). Consoles were used regularly for play across all Gross Motor Function Classification System categories. Conclusion: The potential of games consoles, as home-based virtual reality therapy, in improving the motor function of children with cerebral palsy should be appropriately tested in a randomised controlled trial. Wide ownership, and the relative ease with which children engage in the use of commercially-based virtual reality therapy systems, suggests potential as a means of augmenting therapy protocols, taking advantage of interest and participation patterns of families.